A CRITICAL REVIEW OF INTEGRATING PSYCHOSOCIAL SUPPORT INTO HEALTHCARE SERVICES. - 1Abdulmohsen Masoud Ali Al Warqash, 2Ali HussinAlshai, 3Abdullah Mohammad Alkabeer, 4Abduulaziz Salem Al Farhan, 5Mansor Ahmad Dakam, 6Mohammed Abdullah Hassan Sarar, 7Nasser Ahmad Ali AL Hasnah, 8Abdullah Mahdialzamanan (Chelonian Research Foundation, 2023)
This article looks at the integration of psychosocial factors support into clinical administrations. Psychosocial support is considered a critical component of general well-being care, focusing on the patient’s mental, passionate, and social well-being. This survey investigates the method of reasoning for coordinating mental well-being support into healthcare, the adequacy of different approaches, and execution issues. Fundamental discoveries indicate that compelling mental well-being bolsters patient results, increments patient fulfilment, and diminishes well-being care costs. Be that as it may, issues such as shame, constrained assets, and insufficient instruction stay vital. The article concludes with proposals for approach creators, professionals, and analysts to optimize the integration of mental well-being bolster into services. Keywords: psychosocial support, healthcare services, integration, patient outcomes, challenges, recommendations